Grammatical and syntactical approaches in architecture emerging research and opportunities - Lee, Ju Hyun, 1973- (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series., 2020)
"This book illustrates syntactically derived and grammatically interpolated approaches for architectural configuration, analysis, and design generation"